Importance of an Efficient Warehouse Management System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: In the preview of efficient supply chain management, the warehouse operations play a vital role. The warehouse operation is crucial since it act as the hub were the nodes are connected to the respective spokes. In the current environment it is very much essential to become competitive in a sustainable way. The warehousing operation is the key in order to meet the customers demand and hence it has to be continuously improved. The continuous improvement can be in a way obtained by being flexible in meeting the customers demand based upon their unique requirements. In this article the efficiency of the overall performance of warehouse operation is studied using questionnaire as the tool.